MULTI-MODE RESOURCE CONSTRAINED MULTI PROJECT SCHEDULING PROBLEM OPTIMIZATION WITH SYMBIOTIC ORGANISMS SEARCH - Valentinus Alvin Hodianto; Yang I-Tung (Program Studi Magister Teknik Sipil - Petra Christian University, 2022)
Multi-mode resource-constrained multi project scheduling problem (MRCMPSP) is the extension of standard resource constrained project scheduling problem which considers multiple activity execution modes and multiple projects, subject to precedence and resource constraints. Multiple execution modes allow the activities to have different duration and resource requirement. Furthermore, companies and project managers normally also handle many projects. This study proposed metaheuristic method Symbiotic Organisms Search (SOS) along with random-key (RK) representations, parallel schedule generation scheme (P-SGS), and forward backward scheduling, to find the feasible schedule and minimal project duration of the project portfolio. The evaluation results from standard benchmark instances shows that SOS can get the best solution in most of the tested instances and also achieve better solution in some of them. The validation results from real project case MRCMPSP show that SOS has better performance than other tested metaheuristic methods, namely GA and PSO. Thus, validate the performance of SOS.